Resin Quality Evaluation of Indian Chir Pine Obtained by Bore Hole and Rill Method - Rawat, G. S. (Indian Forester, 2010)
The quality and yield of oleogum resin obtained from chir pine, varies by edaphic, climatic and genetic factors besides the tapping methods. In this context, borehole method of tapping has been found to be more feasible and superior over conventional methods in terms ofmlnimum damage to the tree, and other inputs like time, labour, etc. Physicochemical analysis, based on standard methods of rosin and turpentine separated from chirpine resin samples, was attempted for quality evaluation. The analysis of oleoresin, rosin and turpentine revealed that the borehole tapped oleoresin has less contaminants and better quality with high turpentine as compared to rill tapped oleoresin. This information may be helpful for tapping of high quality resin to the forest managers.